HUBUNGAN TINGKAT KEPATUHAN WANITA USIA SUBUR (WUS) DALAM SKRINING HPV-DNA DENGAN KEJADIAN SUSPECT KANKER SERVIKS DI TOTAL LIFE CLINIC SURABAYA - Asih, Novita Reni; Ilmiah, Widia Shofa; Rayani AW, Tut (NHM PRESS, 2024)
Cervical cancer is the second most common of all cancer cases in Indonesia (Kemenkes RI, 2021). Prevention of cervical cancer can generally be done through routine screening activities and it has been proven that early detection can reduce the incidence rate. The aim of this study was to determine the relationship between the level of compliance of women of childbearing age (WUS) in HPV-DNA screening and the incidence of suspected cervical cancer at Total Life Clinic Surabaya. The design of this research is correlational analytic with a cross sectional approach. The population in this study were all women of childbearing age (WUS) who underwent HPV-DNA examination at the Total Life Clinic Surabaya from July 2022 to December 2023, a total of 38 patients. Total sampling technique. The instruments used in this research were observation sheets and notes made by the researcher. Data analysis uses the contingency test to determine the significance of the relationship between variables. The results showed that the majority of women of childbearing age (WUS) complied with HPV-DNA screening as many as 29 people (76.3%), the incidence of suspected cervical cancer was mostly in the undetected category, namely 34 people (89.5%) and 4 people ( 10.5%) were diagnosed with cervical cancer, there was a relationship between compliance with HPV-DNA screening and the incidence of cervical cancer in WUS at the Total Life Clinic using the contingency coefficient test p-value=0.011. Women who do not comply with cervical cancer screening have a higher risk of being diagnosed with suspected cervical cancer due to delays in detection and treatment of possible precancerous or cancerous conditions. Therefore, it is important to increase awareness, access, and compliance with cervical cancer screening among WUS to reduce this risk.